Multiple in vivo Effects of Cadmium on Photosynthetic Electron Transport in Pea Plants. (30th June 2021) - Todorenko, Daria; Volgusheva, Alena; Timofeev, Nyurgun; Kovalenko, Ilya; Matorin, Dmitry; Antal, Taras
Abstract: The inhibitory effects of cadmium (CdSO4 ) on the primary photosynthetic processes were studied in vivo in Pisum sativum by using Multi‐function Plant Efficiency Analyser (M‐PEA‐2). Photosynthetic parameters related to photosystem (PS) II, PS I and intersystem electron carriers were calculated from the light‐induced kinetics of prompt chlorophyll a fluorescence (OJIP transient), delayed chlorophyll a fluorescence (DF), and 820 nm modulated reflection (MR). Low‐dose exposure to cadmium (20 μm CdSO4 for 48 h) reduced probability of electron transfer from plastoquinones to the terminal electron acceptors of PSI ( δ Ro ) accompanied by a decrease in the rate of P700 + and PC reduction ( V red ) and the magnitude of the I2 step on the DF kinetics. Electron transport through PSI remained unaltered. The obtained results allowed us to propose existence of the potential site of inhibition of photosynthetic electron flow by cadmium between PSII and PSI. We propose to use parameters δ Ro, V red, and I2 /I1 as sensitive indicators of an early contamination by heavy metals. Abstract : Analysis of the high‐resolution kinetics of prompt and delayed chlorophyll fluorescence and 820 nm reflection recorded in leaves of pea plants in the presence of various doses of cadmium showed that the primary photosynthetic response to the toxicant involves inhibition of electron transfer from PSII to the plastoquinone pool (parameters ψ Eo and V red ) and between plastoquinones and PSI (fluorescence and reflection parameters δ Ro, V red, I2 /I1 ). Moderate and high doses of cadmium induced a decrease in PSII photochemistry and a reduction of thylakoid membranes. PSI activity remained unaltered.